O papel dos fatores abióticos e bióticos e dos atributos morfofuncionais na fenodinâmica de Himatanthus bracteatus (A. DC.) Woodson e Himatanthus drasticus (Mart.) Plumel (Apocynaceae) na floresta ciliar do Rio Lençois, Chapada Diamantina, Bahia - Santos, Marília Grazielly Mendes dos (2016)
This research addresses a study of methods of collection and phenological data analysisofHimatanthus bracteatus(A. DC.) Woodson e H. drasticus (Mart.) Plumel(Apocynaceae), and investigate their phenological patterns, relating them to the morphological and functional characters, biotic and abiotic factors. Monthly observations of leaf and reproductive phenology, and herbivory activity of these species were performed. We analyzed the leaf traits, water potential, chlorophyll and wood density (in dry months and rainymonths), and floral biology and floral visitor’s aspects. The normality of the data was tested by setting the corresponding regression and correlation tests. The morphological and functional characters were subjected to analysis of variance, considering each month as a treatment. In this study the quantitative method and the circular analysis were identified as the most appropriate for the intensity analysis and phenological timing of the species. The species were evergreen, with annual flowering and extend fruiting, overlaying all phenophases. Synchrony was note between reproductive phenophases. We identified the Pseudosphinx tetrio as a leaf predator. The precipitation was the trigger for the development of these caterpillars, observed in the host in rainy months. The morphofunctional characters showed water reserves in the stem of both species. The herbivorous activity had relationship with mature leaves and budding.The flowering became more intense in the absence of caterpillars. Thefloral morphology and biologyidentified phalenophily as the pollination syndrome. The aggregation and phenological patterns seems to be related to herbivory and pollination processes ofH. bracteatus and H.drasticus.